Comparative Assessment Of Air-Cooled And Water-Cooled Thermoelectric Power System “Simulation Approach” - Hussin, Muhamad Amirul Aiman (Universiti Sains Malaysia, 2022)
The popularity of hydrocarbon-based power generation systems have dramatically increased in the past few years across many engineering fields. One of the examples of the technology that offers hope in reducing the over consumption of conservative energy sources is the thermoelectric generator. However, because of the physical challenge in optimizing the cooling system, the thermoelectric generator systems typically suffer from having a narrow operating window. This study simulated a thermoelectric power system to assess the performance and combustion characteristics. The thermoelectric generator system was constructed using air-cooled and water cooled heat exchangers. To better optimise the thermal properties of the burner, the discrepancies between the heat capacities of air and water must be properly addressed. The flow complexity of the water-cooled heat exchanger could adversely affect the overall efficiency of the design since it provides a bigger temperature gradient than an air-cooled heat exchanger. In this study, a combustion chamber, an air-cooled heat exchanger, and a water-cooled heat exchanger were designed. Then, the simulation of the combustion chambers was set up and conducted with controlled air mass flow rates to investigate the performance of the combustion chamber based on VCO combustion. The results show that combustion chamber 1 with air mass flow rates of 0.000637kg/s was chosen since it has lower NOx emissions with 5.44x10-8. It also produces a high temperature at the outlet wall with a temperature of 1149.17oC and has an ideal combustion process with an equivalence ratio of 1 that was considered as stoichiometric combustion process. Other simulations were also set up to compare the performance of air-cooled thermoelectric power systems and water-cooled thermoelectric power systems. The results show that the maximum power output was generated by a water-cooled TE power system with 0.628W power output with a temperature difference of 559.86oC compared to an air-cooled TE power system that only generated 0.608W at a temperature difference of 552.72oC. It can thus be concluded that the water-cooled TE power system has a better performance compared to the air-cooled TE power system since the water-cooled TE power system used water as a coolant that has a better thermal conductivity that will efficiently transfer the heat. This research can eventually look into the possibilities of optimizing the power generated.